ANALYZE THE INTENTION TO VISIT TANGKAHAN: A SOCIAL EXCHANGE THEORY APPROACH - Siti Syaprila; Munandar; Ikramuddin; Teuku Zulkarnaen (RADJA PUBLIKA, 2024)
This research aims to analyze the intention to visit Tangkahan: A Social Exchange Theory Approach. Data for this research were collected through a survey method using a questionnaire as the data collection instrument. The respondents used in this study amounted to 114 people. This research employs a quantitative approach with multiple linear regression analysis using SPSS (Statistical Package for the Social Sciences) software. The results of the study indicate that there is a positive and significant influence between the perceived benefits towards the intention to visit Tangkahan Tourism, there is a negative and significant influence between the perceived benefits towards the intention to visit Tangkahan Tourism, there is a negative and significant influence between the perceived risks towards the intention to visit Tangkahan Tourism. Simultaneously, the results of the study show that there is a positive and significant influence between perceived benefits, perceived costs, and perceived risks towards the intention to visit Tangkahan Tourism.